Peran Baznas Kota Padang Panjang Terhadap Pengurangan Peminjaman Pedagang Kepada Rentenir - Cupian Cupian; Mardiyah Hanif; Joval Ifghaniyafi Farras (ITB AAS INDONESIA Surakarta, 2023)
Many traders prefer to borrow from loan sharks rather than safer banking institutions for reasons of convenience and speed. The loan sharks apply high interest which includes riba. One of the efforts to avoid the practice of loan sharks is with productive zakat funds from BAZNAS as business funds. This research aims to to see the influence of the role of BAZNAS in Padang Panjang City including service quality, distribution of zakat, empowerment of mustahik and socialization - education on reducing merchant lending to loan sharks.This research uses a descriptive method with a quantitative approach. The sample is 70 respondents who are traders who receive BAZNAS zakat funds and have also borrowed from loan sharks. The analytical method used is binary logistic regression analysis. From the results of the logistic regression, it was found that the quality of service was significant in reducing the lending of traders to loan sharks, while the distribution of zakat, empowerment of mustahik and socialization - education were not significant in reducing the lending of traders to loan sharks